Acuariidae (Nematoda) in Procellariiformes (Aves) on the southern coast of Rio Grande do Sul, Brazil - Schramm,Camila Costa (2018)
Abstract Acuariidae nematodes are normally found in the digestive tract of aquatic birds, including Procellariiformes. Were examined Calonectris borealis (n = 4), Diomedea exulans (n = 1), Macronectes giganteus (n = 8), Thalassarche chlororhynchos (n = 5), Thalassarche melanophrys (n = 15), Procellaria aequinoctialis (n = 4), Puffinus gravis (n = 2) and Puffinus puffinus (n = 6), collected on the southern coast of RS, Brazil. A total of 16 birds (35.5%) were parasitized by two species of Acuariidae. Stegophorus diomedeae and Seuratia shipleyi were identified, with prevalences of 26.1% and 21.7%, respectively. Few studies on nematodes in Procellariiformes have been conducted. Here, the acuariids Seuratia shipleyi in Calonectris borealis and Procellaria aequinoctialis and Stegophorus diomedeae in Diomedea exulans, Procellaria aequinoctialis and Thalassarche chlororhynchos were reported for the first time.